Analysis of the chemical and physical properties of dried moringa leaves (Moringa oleifera l.) at different drying temperatures using a tray dryer machine - Devi Tanggasari; Nurfaidawati Nurfaidawati; Ahmad Reza Jatnika (Universitas Muhammadiyah Mataram, 2023)
Moringa or (Moringa oleifera l.) is a very common plant in tropical and subtropical climates. West Nusa Tenggara is one of the areas with a relatively high level of drought, where the dry season is relatively longer than the rainy season. This affects the type and character of plants in the West Nusa Tenggara region in adapting to these climatic conditions. One of them is the moringa plant which easily adapts to hot weather and altitude above sea level. Moringa is a plant with various benefits, such as food, medicine, cosmetics, and others. The purpose of this study was to analyze the effect of different drying temperatures on the chemical and physical properties of dried Moringa leaves using a tray dryer. This study used a 1-factor Completely Randomized Design (CRD) with three temperature treatments for 2 hours of drying with three replications. The temperature treatments in the study were: 45°C, 50°C and 55°C for 2 hours. The research results from the analysis of the chemical properties of dried moringa leaves from the three temperature treatments can be seen that the effective temperature treatment at 55°C, namely: water content (21.67%), ash content (0.51%), protein content (19.43%). The results of the analysis of the physical properties of the color test using the Colorimeter application showed that the highest value was at 50°C with a value of (77.93) and the organoleptic test of the panelist's preference level for the texture of dried Moringa leaves was seen at 55°C with a value of (4.08).